Intraosseous lipoma of the patella: a case report and review of the literature - Castañeda Martinez, Adriana Ivette; Pala, Elisa; Cappellesso, Rocco; Trovarelli, Giulia; Ruggieri, Pietro (Acta Biomedica Atenei Parmensis, 2021)
An intraosseous lipoma is considered one of the rarest primary bone tumors. The etiology of this lesion remains unclear; many lesions are asymptomatic and appear only as incidental findings during routine radiographic evaluations. Magnetic resonance imaging of intraosseous lipomas can help to establish a diagnosis and to stage the neoplasm. This is a case report of a 53-year old man with a rare intraosseous lipoma of the patella.